Maillard Degradation Pathways of Vitamin C. Issue 18 (28th March 2013) - Smuda, Mareen; Glomb, Marcus A.
<x xml:space="preserve">Abstract</x> Degradation mechanisms: 75 % of the Maillard degradation pathways of ascorbic acid can be explained by oxidative α fragmentation (31 %), β cleavage (32 %), and decarboxylation from hydrate/hemiaminal intermediates (12 %), which lead to carbonyl and dicarbonyl compounds, carboxylic acids, and amide advanced glycation endproducts. The results are a major step forward in the understanding of changes occurring in systems containing vitamin C.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>